2011
DOI: 10.1117/1.3598847
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy, at 60 J/cm2 associated with a Biosilicate® increase in bone deposition and indentation biomechanical properties of callus in osteopenic rats

Abstract: We investigate the effects of a novel bioactive material (Biosilicate(®)) and low-level laser therapy (LLLT), at 60 J/cm(2), on bone-fracture consolidation in osteoporotic rats. Forty female Wistar rats are submitted to the ovariectomy, to induce osteopenia. Eight weeks after the ovariectomy, the animals are randomly divided into four groups, with 10 animals each: bone defect control group; bone defect filled with Biosilicate group; bone defect irradiated with laser at 60 J/cm(2) group; bone defect filled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 21 publications
0
21
1
5
Order By: Relevance
“…The irradiation frequency was based on similar studies in which bone healing after LLLT was evaluated. 16,36 Most of the studies were performed for five sessions per week. However, different treatment application protocols were reported for LLLT at different powers for bone healing.…”
mentioning
confidence: 99%
“…The irradiation frequency was based on similar studies in which bone healing after LLLT was evaluated. 16,36 Most of the studies were performed for five sessions per week. However, different treatment application protocols were reported for LLLT at different powers for bone healing.…”
mentioning
confidence: 99%
“…Considerando os critérios de inclusão adotados, foram encontrados um total de 30 estudos nas bases de dados consultadas, dos quais quinze (50%) foram realizados em tendão 3,4,6,9,[22][23][24][31][32][33][34][35][36][37][38] , dez (33,33%) em musculos 12,14,[39][40][41][42][43][44][45] , e cinco (16,66%) em osso e/ou articulação 13,25,[46][47][48] Os resultados mais expressivos obtidos com a terapia foram: diminuição da resposta inflamatória mediante redução de células inflamatórias e modulação de mediadores da inflamação (36,66%), e o aumento da síntese de colágeno (13,33%). Alguns dos demais resultados (50,01%) mencionados foram: angiogênese; redução do estresse oxidativo, do colágeno e da fibrose; aumento do tecido de granulação, da remodelação e síntese óssea, assim como da expressão da proteína da diferenciação miogênica (MyoD) e do fator de crescimento endotelial vascular (VEGF).…”
Section: Resultsunclassified
“…Os condroblastos são células que secretam componentes da matriz extracelular para a formação da estrutura cartilaginosa, enquanto os osteoblastos participam da síntese dos componentes da matriz óssea, expressam fosfatase alcalina, enzima que permite a mineralização da matriz, e inclusive secretam fatores de crescimento. Fangel et al 46 e Fernandes et al 48 também descreveram aumento da síntese óssea após tratamento com laserterapia na tíbia de ratos. Os autores observaram, mediante avaliação histopatológica, neoformação óssea particularmente na análise realizada cinco dias após lesão traumática e tratamento.…”
Section: Discussionunclassified
“…In another study, LLLT (685nm, 35mW, 10 J/cm 2 ) demonstrated positive photobiomodulation effects as evidenced by stimulated vascularization, fibroblast proliferation and collagen deposition at its initial stages of bone tissue regeneration surrounding the nanomaterial based implants (poly-L-lactic/ polyglycolic acid) in the femur of rats (Freddo et al, 2009). Besides reducing inflammation, when LLLT (830nm, 100 mW/cm 2 , 60 J/cm 2 ) was used post-surgery for bone-fracture consolidation in tibias of osteoporotic rats, in conjunction with Biosilicate®, (a fully crystallized bioactive glass ceramic fillers), a significantly increased deposition of new bone tissue and improved biomechanical properties were observed compared to without nanomaterial-assisted device (Fangel et al, 2011). Nissan et al (2006) demonstrated that GaAs laser-therapy (904nm, 0,72 J, 4 mW/cm 2 ) resulted in new bone formation around hydroxyapatite implants and led to significant increase in the total bone area in rat mandibles by affecting calcium transport during new bone formation (Nissan et al, 2006).…”
Section: Phototherapy In Conjunction With Nanotechnology Used For mentioning
confidence: 99%